The Impact of Digital Banking, Motivation, Training and Leadership on Employee Performance - Astarizal, Astarizal; Ngaliman, Ngaliman; Windayati, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2023)
This research aims to determinane the effect of dependent variable Y (employee performance). Meanwhile, the independent variables are X1 (digital banking), X2 (motivation), X3 (training) and X4 (leadership) at PT. Bank Central Asia Batam Branch. The population is all employees of PT Bank Central Asia Batam Branch, totaling 135 employees. Samples were taken using the Slovin formula with an e value of 5% so that the samples processed in the research were 100 employees. The data analysis technique was processed using the Statistical Product and Service Solution (SPSS) version 25 program application. The results of data analysis produced a multiple linear regression equation Y=11.529+0.247X1+0.464X2 - 0.010X3+0.147X4 + e. The value of each independent variable, namely digital banking, is 0.168 > 0.05, motivation is 0.000 < 0.05, training is 0.933 > 0.05 and leadership is 0.181 > 0.05. The results of the regression analysis show that the digital banking, training and leadership variables have a partial positive and insignificant influence, while motivation has a positive and significant influence on employee performance. Independent variable simultaneously provides a positive and significant contribution to Y (employee performance) with a degree of significance (Sig F) of 0.000 on employee performance < 0.05